Gas Capture Processes - Zhang, Zhien; Borhani, Tohid; El-Naas, Muftah; Soltani, Salman; Yan, Yunfei (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book introduces the recent technologies introduced for gases capture including CO2, CO, SO2, H2S, NOx, and H2. Various processes and theories for gas capture and removal are presented. The book provides a useful source of information for engineers and specialists, as well as for undergraduate and postgraduate students in the fields of environmental and chemical science and engineering.